The Impact and Handling of Criminal Law on Trademark Counterfeiting in Medan City (Study of Medan District Court Decision No. 2152/Pid.Sus/2024/PN Mdn) - Sitorus, Raja Pranata; Mahmud Mulyadi; Saidin (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
Trademark counterfeiting is a form of crime that has serious impacts on the business world and consumers. In the era of global and digital trade, the existence of brands is very vital. Therefore, brand protection through a criminal law approach is absolutely necessary. Effective and responsive law enforcement in Medan City is an important representation in providing legal certainty and protection of intellectual property rights in Indonesia's regions. The crime of trademark counterfeiting is a form of violation of Intellectual Property Rights (IPR), especially trademark rights. This counterfeiting occurs when someone uses the same or similar brand to a registered brand owned by another party without permission, thereby harming the rightful owner and misleading consumers. In Indonesian positive law, this act is regulated in Law Number 20 of 2016 concerning Trademarks and Geographical Indications, specifically Article 100 paragraphs (1) and (2), and can be expanded by the application of Article 263 of the Criminal Code if accompanied by the use of false documents. Based on the objective and subjective elements in criminal law and Moeljatno's opinion, trademark counterfeiting meets the qualifications as a criminal act. In the Medan District Court Decision No. In case No. 2152/Pid.Sus/2024/PN Mdn, the panel of judges found the defendant guilty of using the “Yamalube” brand without permission from PT Yamaha Indonesia Motor Manufacturing, with visual evidence resembling the original product. The judge sentenced him to prison, a fine, and ordered the destruction of evidence. However, law enforcement in Medan City faces obstacles, such as the nature of the complaint offense, differing legal interpretations, weak coordination among law enforcement officials, the prevalence of counterfeit products in the market, and low legal awareness among business actors and consumers. This demonstrates the need for preventive and coordinated efforts to optimize brand protection.